A survey of autistic adults, relatives and clinical teams in the United Kingdom: And Delphi process consensus statements on optimal autism diagnostic assessment for adults. (November 2022) - Wigham, Sarah; Ingham, Barry; Le Couteur, Ann; Wilson, Colin; Ensum, Ian; Parr, Jeremy R
Accessing adult autism diagnostic pathways can be difficult. This study explored perspectives of UK autistic adults, relatives and clinicians regarding the characteristics of optimal adult autism assessment and diagnostic services. In stage 1, three key stakeholder groups were surveyed about experiences of adult autism diagnostic services (pre-assessment/assessment): 343 autistic adults, 45 relatives and 35 clinicians completed parallel surveys. Information from stage 1 surveys was used to devise statements for a modified Delphi process in stage 2 seeking consensus among clinicians on optimal diagnostic service characteristics. Data analyses were non-parametric and descriptive. Over half of adults were in contact with mental health services prior to autism diagnosis. Clinicians reported that multidisciplinary diagnostic teams lacked key professionals. Thirteen statements describing optimal autism diagnostic service provision were developed. There was consensus from clinicians on 11 statements relating to clear assessment pathways, updates for people while waiting, pre-assessment information gathering/provision, co-occurring condition identification and training/networking. Some autistic adults, relatives and clinicians were positive about services, all stakeholders identified improvements were needed. The findings describing optimal service provision are relevant for UK clinicians, managers and commissioners to improve diagnostic assessments for autistic adults, and have international relevance for similar health systems. Lay abstract: Living with undiagnosed autism can be distressing and may affect mental health. A diagnosis of autism can help self-awareness and self-understanding. However, it can be difficult for adults to access an autism assessment. Clinicians also sometimes find it hard to identify autism in adults. This may mean an autism diagnosis is delayed or missed. In this study, we asked autistic adults, relatives and clinicians how to improve this. The study was in two stages. In the first stage (stage 1), 343 autistic adults and 45 relatives completed a survey. In the survey, we asked questions about people's experiences of UK autism assessment services for adults. Thirty-five clinicians completed a similar survey. Clinicians reported that some autism assessment teams lacked key professionals, for example, psychologists and occupational therapists. We used the information from the three separate surveys to create 13 statements describing best autism assessment services for adults. In stage 2, we asked clinicians for their views on the 13 statements. Clinicians agreed with 11 of the statements. Some autistic adults, relatives and clinicians were positive about autism assessment services, and many also described areas that could be improved. The study findings can be used to improve UK adult autism assessment services and may be helpful for service developments worldwide.